Stock returns and expected business conditions: Half a century of direct evidence - Sean D. Campbell; Francis X. Diebold (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We explore the macro/finance interface in the context of equity markets. In particular, using half a century of Livingston expected business conditions data we characterize directly the impact of expected business conditions on expected excess stock returns. Expected business conditions consistently affect expected excess returns in a statistically and economically significant counter-cyclical fashion: depressed expected business conditions are associated with high expected excess returns. Moreover, inclusion of expected business conditions in otherwise standard predictive return regressions substantially reduces the explanatory power of the conventional financial predictors, including the dividend yield, default premium, and term premium, while simultaneously increasing R2. Expected business conditions retain predictive power even after controlling for an important and recently introduced non-financial predictor, the generalized consumption/wealth ratio, which accords with the view that expected business conditions play a role in asset pricing different from and complementary to that of the consumption/wealth ratio. We argue that time-varying expected business conditions likely capture time-varying risk, while time-varying consumption/wealth may capture time-varying risk aversion.
urn:nbn:de:hebis:30-18120
Keywords: G12; 330; Business Cycle; Expected Equity Returns; Prediction; Livingston Survey; Risk Aversion; Equity Premium; Risk Premium; Konjunkturprognose; Aktienmarkt; Kapitalertrag; Risikoprämie; Geschäftsklima; Theorie; USA